Answer:
it is makeing me do it
Step-by-step explanation:
Answer:
-3
Step-by-step explanation:
(fg)(-1) is just f(-1) * g(-1). From the graph on the left, we can see that f(-1) is 1, since (-1,1) is on the graph. From the graph on the tight, we can see that g(-1) is -3, since (-1,-3) is on the graph. Now, we just have to multiply 1 and -3: 1*-3 = -3
Answer: (11, 7.5)
Step-by-step explanation:
((8, 12)+(14, 3))/2=
(8+14, 12+3)/2=
(22/2, 15/2)=(11, 7.5)
<u>240 cm</u>³
volume of rectangular prism:
Length * Width * Height
4 cm * 20 cm * 3 cm
240 cm³